Development of a new evidence-based communication curriculum at at Danish medical school: Presenter(s): Christina Louise Lindhardt, The Department of Clinical Institute, University of Southern Denmark, Denmark. (April 2023) - Hvidt, Elisabeth Assing; Ammentorp, Jette
Abstract : Background: Research evidence unequivocally shows that poor communication competencies among health professionals lead to diagnostic errors and an increase in malpractice complaints. Therefore, communication training initiatives, and the ability to measure their effects, has been called for in hospital- and medical educational settings. We are presenting the strategies of a joined working group further developing and optimizing the communication curriculum at the medical school of the University of Southern Denmark. Methods: The working group, consisting of researchers and clinicians with expertise in patient communication, reviewed the existing communication curriculum focusing on how to increase teaching elements centering on relationship-building, patient-centred communication, digital communication skills and student vulnerabilities. Results: A design for an optimized curriculum was developed, targeting both bachelor- and graduate students. Initiating the communication training, first semester students participate in a communication workshop where communication is emphasized as foundational for medical practice through reflective exercises and training. Communication modules in bachelor- and graduate courses, using patient actors, is supplemented with blended learning practices. A second workshop is positioned at the graduate level, focusing on students' mental well-being, vulnerabilities and self-compassion following clinical rotations. The final draft of the curriculum as well as a discussion will be available for presentation at the conference in September 2022.